Positive electrode material composition, secondary battery and electric device
Patent Information
- Application Number
- CN202380042172.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2024-12-31
AI Technical Summary
During the cycling process of existing lithium-ion batteries, the crystal structure of the cathode material deteriorates, resulting in insufficient battery charging capacity and energy density. It performs poorly especially under low temperature conditions and cannot effectively improve charging capacity.
A combination of a phosphate-based cathode material and a ternary cathode material is used. By adjusting the ratio and structural characteristics of the two, the stability of the phosphate-based material and the high energy density of the ternary material are used, combined with the polycrystalline secondary ball structure and Doping elements, optimizing particle size distribution and specific surface area, improving charging capacity and cycle performance.
It significantly improves the energy density, cycle performance and low-temperature discharge capability of lithium-ion batteries, improves fast charging performance and structural stability, and extends the service life of the battery.
Smart Images

Figure CN119234332A_ABST
Abstract
Description
Positive electrode material composition, secondary battery and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material composition, a secondary battery, and an electrical device. Background Art
[0002] Lithium-ion batteries are secondary batteries (rechargeable batteries) that rely primarily on the movement of lithium ions between the positive and negative electrodes. During the charge and discharge process, lithium ions are intercalated and deintercalated between the two electrodes. During charging, lithium ions are deintercalated from the positive electrode and then intercalated into the negative electrode through the electrolyte, leaving the negative electrode in a lithium-rich state. The reverse occurs during discharge.
[0003] Currently, there are many methods for improving the cycle performance of lithium-ion batteries. These include modifying the cathode material by doping or coating it to slow down the deterioration of its crystal structure during cycling. Alternatively, cathode materials with different advantages can be combined to leverage their strengths and offset their weaknesses to improve the battery's cycle performance and energy density. For example, combining lithium iron phosphate cathode materials with ternary cathode materials can improve the battery's cycle performance or energy density to a certain extent, but it cannot improve the battery's rechargeability.
[0004] Summary of the Invention
[0005] The present application provides a positive electrode material composition, a secondary battery and an electrical device to improve the fast charging performance of the battery.
[0006] According to the first aspect of the present application, a positive electrode material composition is provided, including a phosphate-based positive electrode material and a ternary positive electrode material, the weight of the phosphate-based positive electrode material is denoted as W1, the weight of the ternary positive electrode material is denoted as W2, α=W1 / (W1+W2), 50%≤α≤97%, optionally 70%≤α≤90%, the phosphate-based positive electrode material is a polycrystalline secondary sphere material and / or the ternary positive electrode material is a polycrystalline secondary sphere material.
[0007] Phosphate-based cathode materials have phosphate polyanion materials, so they have strong stability, good cycle stability, and life advantages; ternary cathode materials have high energy density, but the layered transition metal oxides are structurally unstable during the cycle process, resulting in a poorer lifespan of the ternary cathode materials than the phosphate-based ones. After the two are mixed, the high energy density of the ternary cathode material is used to compensate for the low energy density of the phosphate-based cathode material, and the advantage of the strong stability of the phosphate-based cathode material is used to compensate for the poor structural stability of the ternary cathode material. At the same time, by adjusting the ratio of the two, a synergistic effect of the two can be achieved, so that the cathode material composition of the present application has the advantages of higher energy density and higher cycle performance. Moreover, the phosphate-based cathode material and / or ternary cathode material of the present application are polycrystalline secondary spheres, which fully utilize the advantage of the small bulk diffusion impedance in the polycrystalline secondary spheres, thereby improving the charging capacity and low-temperature discharge capacity of the composition.
[0008] In any embodiment of the first aspect, D of the positive electrode material composition V 50≥8μm, optionally, the particle size distribution of the above-mentioned positive electrode material composition satisfies the following relationship: 14>Aα+B(1-α)>7, wherein A is the DV of the phosphate-based positive electrode material 50 , B is the DV of the ternary cathode material 50 α is the proportion of lithium manganese iron phosphate cathode material. Further improving the particle size coordination between phosphate-based cathode materials and ternary cathode materials will significantly enhance fast charging capability and low-temperature discharge efficiency.
[0009] In any embodiment of the first aspect, the particle size of the primary particles of the above-mentioned phosphate-based positive electrode material is 10 to 600 nm, and can be optionally 35 to 110 nm. Selecting a phosphate-based positive electrode material with a primary particle size of nanometer level can further improve the rate performance of the phosphate-based positive electrode material.
[0010] In any embodiment of the first aspect, optionally, the laser particle size D of the phosphate-based cathode material V 50 is 7~30μm, D V 50 can be selected from 8 to 14 μm, D V 90<30μm. Select laser particle size D V 50 Within the above range, the agglomeration of primary particles is more stable, thereby further improving the structural stability of the phosphate-based positive electrode material.
[0011] In any embodiment of the first aspect, optionally, the BET specific surface area of the phosphate-based positive electrode material is 8-20 m 2 / g.
[0012] In any embodiment of the first aspect, optionally, the compaction density of the phosphate-based positive electrode material is 1.5 to 2.6 g / cm3 , compaction density can be selected from 2.15 to 2.5 g / cm 3 . To further improve the rate performance of the composition.
[0013] In any embodiment of the first aspect, optionally, the specific capacity of the phosphate-based positive electrode material at a rate of 0.1C is 140-165 mAh / g, optionally 155-160 mAh / g.
[0014] In any first embodiment of the first aspect, the chemical formula of the phosphate-based positive electrode material is Li 1+x Mn 1- y A y P 1-z R z O4, in the chemical formula, x is any value in the range of -0.100-0.100, y is any value in the range of 0.001-0.500, and z is any value in the range of 0.001-0.100, and the values of x, y, and z satisfy the following conditions: the chemical formula maintains electrical neutrality; A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and can be optionally one or more elements selected from Fe, Ti, V, Ni, Co, and Mg; R is one or more elements selected from B, Si, N, S, F, Cl, and Br, and optionally, R is an element selected from B, Si, N, and S. Doping the phosphate system with the elements A and R helps to improve the structural stability of the phosphate-based positive electrode material and the rate performance of the secondary battery having the same.
[0015] In any first embodiment of the first aspect, the chemical formula of the phosphate-based positive electrode material is Li a A x Mn 1-y B y P 1- z C z O 4-n D n, wherein the A comprises one or more elements from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W, the B comprises one or more elements from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge, the C comprises one or more elements from the group consisting of B (boron), S, Si, and N, the D comprises one or more elements from the group consisting of S, F, Cl, and Br, the a is selected from the range of 0.9 to 1.1, the x is selected from the range of 0.001 to 0.1, the y is selected from the range of 0.001 to 0.5, the z is selected from the range of 0.001 to 0.1, the n is selected from the range of 0.001 to 0.1, and the phosphate-based positive electrode material is electrically neutral. By doping the above-mentioned specific elements at the above-mentioned four positions at the same time in specific amounts, the rate performance, cycle performance, and / or high-temperature stability of the phosphate-based positive electrode material can be significantly improved.
[0016] In any embodiment of the first aspect, the phosphate-based cathode material optionally includes a polycrystalline core and a coating layer covering the polycrystalline core, wherein the polycrystalline core has a chemical formula of Li 1+x Mn 1-y A y P 1-z R z O4 or chemical formula Li a A x Mn 1-y B y P 1-z C z O 4- n D n The coating layer can be one or more layers of pyrophosphate, phosphate, or carbon. The coating layer can effectively inhibit the dissolution of transition metals and reduce surface side reactions of phosphate-based cathode materials.
[0017] In any embodiment of the first aspect, D of the above-mentioned ternary positive electrode material V 50 is 5~11μm, D V 99≤30μm; Optionally, the average particle size of the primary particles of the ternary cathode material is 50-800nm. The ternary material is made into secondary particles, which can further shorten the lithium ion diffusion path and bulk diffusion resistance.
[0018] In any embodiment of the first aspect, the BET specific surface area of the ternary cathode material is 0.2 to 1.2 m 2 / g, and the BET specific surface area of the ternary material is within the above range. By controlling the compactness of the secondary particles, the compaction is improved, thereby increasing the energy density of the material.
[0019] In any embodiment of the first aspect, the ternary cathode material is an NCM ternary cathode material or an NCA ternary cathode material. Optionally, the molar content of Ni in the ternary cathode material is 50% - 75%, and the molar content of Co is 0.5% - 49.5%. Further optionally, the molar content of Ni is 50% - 70%, and the molar content of Co is 5% - 35%. The molar content of Ni affects the capacity of the ternary cathode material and has a great impact on improving the energy density of the blended material. The increase in the molar content of Co can improve the electronic conductivity and ionic conductivity of the system, and can effectively improve the charging ability of the ternary cathode material.
[0020] In any embodiment of the first aspect, the ternary cathode material has the chemical formula Li a’ Ni b’ Co c’ M1 d’ M2 e’ O f’ R′ g’ , where 0.75 ≤ a’ ≤ 1.2, 0 < b’ < 1, 0 < c’ < 1, 0 < d’ < 1, 0 ≤ e’ ≤ 0.2, 1 ≤ f’ ≤ 2.5, 0 ≤ g’ ≤ 1, f’ + g’ ≤ 3, M1 is Mn element and / or Al element, M2 is one or more elements selected from Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R′ is one or more elements selected from N, F, S, Cl. Element doping is used to improve the cycle performance and rate performance of the ternary cathode material.
[0021] According to the second aspect of the present application, a secondary battery is provided. The secondary battery includes a positive electrode plate, and the positive electrode plate includes a positive electrode active material, which is any one of the positive electrode material compositions in the first aspect above. The secondary battery with the positive electrode material composition of the present application effectively improves the charging ability and low-temperature discharge ability on the basis of high energy density and cycle performance.
[0022] According to the third aspect of the present application, an electrical device is provided, including a secondary battery, and the secondary battery is selected from the secondary batteries in the second aspect. The electrical device has better working stability at low temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required to be used in the embodiments of the present application will be briefly introduced below. Obviously, the following described drawings are only some embodiments of the present application. For those of ordinary skill in the art, other drawings can be obtained according to the drawings without creative efforts.
[0024] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application.
[0025] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 1 .
[0026] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0027] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.
[0028] FIG. 5 is an exploded view of the battery pack shown in FIG. 4 according to an embodiment of the present application.
[0029] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0030] In the drawings, the drawings are not drawn to scale.
[0031] Description of reference numerals:
[0032] 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0033] The following detailed description of the embodiments of the present application is provided in conjunction with the accompanying drawings and examples. The following detailed description of the embodiments and the accompanying drawings are used to illustrate the principles of the present application, but are not intended to limit the scope of the present application, that is, the present application is not limited to the described embodiments.
[0034] Below, the embodiments of the positive electrode material composition, secondary battery and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0035] The "ranges" disclosed herein are defined in terms of lower and upper limits, where a given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values and can be combined arbitrarily, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 to 120 and 80 to 110 are listed for a particular parameter, it is understood that ranges of 60 to 110 and 80 to 120 are also contemplated. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, the following ranges are all contemplated: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise indicated, the numerical range "a to b" is a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0036] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0039] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0040] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0041] [Secondary battery]
[0042] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged to activate the active materials after discharge and continue to be used.
[0043] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the battery's charge and discharge process, active ions (such as lithium ions) are embedded and released back and forth between the positive and negative electrode sheets. The separator is set between the positive and negative electrode sheets, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte between the positive and negative electrode sheets mainly plays the role of conducting active ions.
[0044] [Cathode material]
[0045] A typical embodiment of the present application provides a positive electrode material composition, including a phosphate-based positive electrode material and a ternary positive electrode material, the weight of the phosphate-based positive electrode material is recorded as W1, the weight of the ternary positive electrode material is recorded as W2, α=W1 / (W1+W2), 50%≤α≤97%, optionally 70%≤α≤90%, the phosphate-based positive electrode material is a polycrystalline secondary sphere material and / or the ternary positive electrode material is a polycrystalline secondary sphere material.
[0046] Phosphate-based cathode materials have phosphate polyanion materials, so they have strong stability, good cycle stability, and life advantages; ternary cathode materials have high energy density, but the layered transition metal oxides are structurally unstable during the cycle process, resulting in a poorer lifespan of the ternary cathode materials than the phosphate-based ones. After the two are mixed, the high energy density of the ternary cathode material is used to compensate for the low energy density of the phosphate-based cathode material, and the advantage of the strong stability of the phosphate-based cathode material is used to compensate for the poor structural stability of the ternary cathode material. At the same time, by adjusting the ratio of the two, a synergistic effect of the two can be achieved, so that the cathode material composition of the present application has the advantages of higher energy density and higher cycle performance. Moreover, the phosphate-based cathode material and / or ternary cathode material of the present application are polycrystalline secondary spheres, which fully utilize the advantage of the small bulk diffusion impedance in the polycrystalline secondary spheres, thereby improving the charging capacity and low-temperature discharge capacity of the composition.
[0047] The positive electrode sheets are cut by argon ion polishing, and the elemental analysis is performed on the planed surface. The main element ratios of the lithium manganese iron phosphate material and the ternary material are then compared, and the ratios are then converted to weight.
[0048] In some embodiments, the D of the positive electrode material composition is V 50≥8μm, optionally, the particle size distribution of the above-mentioned positive electrode material composition satisfies the following relationship: 30>1 / {Aα+B(1-α)}>7, wherein A is the D of the phosphate-based positive electrode material V 50, B is the D of the ternary cathode material V 50. Further improve the particle size matching effect between phosphate-based cathode materials and ternary cathode materials, thereby significantly improving fast charging capability and low-temperature discharge efficiency.
[0049] In some embodiments, the particle size of the primary particles of the above-mentioned phosphate-based positive electrode material is 10 to 600 nm, and can be optionally 35 to 110 nm. Selecting a phosphate-based positive electrode material with a primary particle size of nanometer level can further improve the fast charging capability and low-temperature discharge efficiency of the phosphate-based positive electrode material.
[0050] In some embodiments, optionally, the laser particle size D of the phosphate-based cathode material is V 50 is 7~30μm, D V 50 can be selected from 8 to 14 μm, D V 90<30μm. Select laser particle size D V Within the above range, the agglomeration of primary particles is more stable, thereby further improving the structural stability of the phosphate-based cathode material, thereby further improving the cycle performance of the cathode material composition. The above laser particle size is the laser particle size of the secondary spheres of the phosphate-based cathode material.
[0051] In some embodiments, optionally, the BET specific surface area of the phosphate-based cathode material is 8-20 m 2 / g. To further control its cycle performance within a more ideal range.
[0052] In some embodiments, optionally, the compaction density of the phosphate-based cathode material is 1.5 to 2.6 g / cm 3 , compaction density can be selected from 2.15 to 2.5 g / cm 3 . To further improve the rate performance of the composition.
[0053] In some embodiments, optionally, the specific capacity of the phosphate-based cathode material at a rate of 0.1C is 140-165 mAh / g, optionally 155-160 mAh / g.
[0054] In the first embodiment, the chemical formula of the phosphate-based positive electrode material is Li 1+x Mn 1-y A y P 1-z R z O4, in the chemical formula, x is any value in the range of -0.100-0.100, y is any value in the range of 0.001-0.500, and z is any value in the range of 0.001-0.100, and the values of x, y, and z satisfy the following conditions: the chemical formula maintains electrical neutrality; A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and can be optionally one or more elements selected from Fe, Ti, V, Ni, Co, and Mg; R is one or more elements selected from B, Si, N, S, F, Cl, and Br, and optionally, R is an element selected from B, Si, N, and S. The element A doped at the manganese position of the lithium manganese phosphate helps to reduce the lattice change rate of the lithium manganese phosphate during the lithium insertion and extraction process, improves the structural stability of the lithium manganese phosphate positive electrode material, greatly reduces the dissolution of manganese, and reduces the oxygen activity on the particle surface. The element R doped at the phosphorus position helps to change the difficulty of the Mn-O bond length change, thereby reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the rate performance of the secondary battery.
[0055] In some embodiments, the chemical formula of the phosphate-based cathode material is Li a A x Mn 1-y B y P 1-z C z O 4-n D n, wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W, B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge, C includes one or more elements selected from the group consisting of B (boron), S, Si, and N, D includes one or more elements selected from the group consisting of S, F, Cl, and Br, a is selected from the range of 0.9 to 1.1, for example, 0.97, 0.977, 0.984, 0.988, 0.99, 0.991, 0.992, 0.993, 0.994, 0.995, 0.996, 0.997, 0.998, 1.01, and x is selected from the range of 0.001 to 0.1 , for example, 0.001, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, y is selected from the range of 0.001 to 0.5, for example, 0.001, 0.005, 0.02, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.34, 0.345, 0.349, 0.35, 0.4, 0.5, z is selected from the range of 0.001 to 0.1, for example, 0.001, 0.005, 0.08, 0.1, n is selected from the range of 0.001 to 0.1, for example, 0.001, 0.005, 0.08, 0.1, and the phosphate-based positive electrode material is electrically neutral. A, B, C, and D are elements doped at the Li, Mn, P, and O positions of the compound LiMnPO4, respectively. Without wishing to be bound by theory, it is currently believed that the performance improvement of phosphate-based cathode materials is related to reducing the lattice change rate and surface activity of phosphate-based cathode materials during lithium insertion and extraction. Reducing the lattice change rate can reduce the lattice constant difference between the two phases at the grain boundary, reduce interfacial stress, and enhance Li +The transport capacity at the interface improves the rate performance of the positive electrode active material. However, high surface activity can easily lead to serious side reactions at the interface, exacerbating gas production, electrolyte consumption and interface damage, thereby affecting the cycle performance of the battery. The above-mentioned phosphate-based positive electrode material reduces the lattice change rate by doping with Li and Mn sites. Mn site doping also effectively reduces surface activity, thereby inhibiting Mn dissolution and side reactions at the interface between the positive electrode active material and the electrolyte. P-site doping makes the change rate of the Mn-O bond length faster, reduces the migration barrier of the small polaron of the material, and is beneficial to electronic conductivity. O-site doping has a good effect on reducing side reactions at the interface. P-site and O-site doping also affect the Mn dissolution and kinetic properties of antisite defects. Therefore, doping reduces the concentration of antisite defects in the material, improves the kinetic properties and specific capacity of the material, and can also change the morphology of the particles, thereby increasing the compaction density. The applicant has unexpectedly discovered that by simultaneously doping specific elements in specific amounts at the Li, Mn, P, and O positions of the LiMnPO4 compound, significantly improved rate performance can be achieved, while significantly reducing the dissolution of Mn and the doping element at the Mn position, resulting in significantly improved cycle performance and / or high-temperature stability, and the gram capacity and compacted density of the material can also be increased.
[0056] In some embodiments, the phosphate-based cathode material optionally includes a polycrystalline core and a coating layer covering the polycrystalline core, wherein the polycrystalline core has a chemical formula of Li 1+x Mn 1-y A y P 1-z R z O4, the coating layer can optionally be one or more layers of pyrophosphate, phosphate, and carbon. Since the migration barrier of transition metals in pyrophosphate is relatively high (>1eV), the dissolution of transition metals can be effectively inhibited. Phosphate has excellent lithium ion conductivity and can reduce the surface impurity lithium content. The carbon layer can effectively improve the electrical conductivity and desolvation ability of LiMnPO4, and can also act as a "barrier" to further hinder the migration of manganese ions into the electrolyte and reduce the corrosion of the electrolyte to the active material; at the same time, the above-mentioned carbon layer in the mixture can also optimize the conductive network around the ternary positive electrode material and improve the mixing uniformity of the phosphate-based positive electrode material and the ternary positive electrode material.
[0057] In some embodiments, the D of the above-mentioned ternary cathode material V 50 is 5-11 μm, DV99 ≤ 30 μm; optionally, the average particle size of the primary particles of the ternary cathode material is 50-800 nm. The ternary material is made into secondary particles, which can further shorten the lithium ion diffusion path and bulk diffusion resistance.
[0058] Generally, the specific surface area of secondary particles is larger than that of primary particles with the same particle size. Therefore, the interfacial side reactions are severe, resulting in the consumption of active lithium and deteriorating the battery life. To avoid the above problems caused by secondary particles, in some embodiments, the BET specific surface area of the above ternary cathode material is 0.2-1.2 m 2 / g. By selecting a ternary material with a BET specific surface area within the above range and controlling the compactness of the secondary particles, the compaction can be improved, and thus the energy density of the material can be increased.
[0059] In some embodiments, the above ternary cathode material is an NCM ternary cathode material or an NCA ternary cathode material. Optionally, the molar content of Ni in the ternary cathode material is 50%-75%, and the molar content of Co is 0.5%-49.5%; further optionally, the molar content of Ni is 50%-70%, and the molar content of Co is 5%-35%. The molar content of Ni affects the capacity performance of the ternary cathode material and has a great impact on improving the energy density of the blended material. The molar content of Co can improve the electronic conductivity and ionic conductivity of the system and can effectively improve the kinetics of the ternary cathode material.
[0060] In some embodiments, the above ternary cathode material has the chemical formula Li a’ Ni b’ Co c’ M1 d’ M2 e’ O f’ R′ g’ , where 0.75 ≤ a’ ≤ 1.2, 0 < b’ < 1, 0 < c’ < 1, 0 < d’ < 1, 0 ≤ e’ ≤ 0.2, 1 ≤ f’ ≤ 2.5, 0 ≤ g’ ≤ 1, f’ + g’ ≤ 3, M1 is Mn element and / or Al element, M2 is one or more elements selected from Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R′ is one or more elements selected from N, F, S, Cl. Element doping is used to improve the cycle performance and rate performance of the ternary cathode material.
[0061] According to some embodiments of the present invention, the preparation method of the phosphate-based cathode material Li 1+x Mn 1-y A y P 1-z R z O4 includes:
[0062] Mixing and stirring a manganese source, a source of element A, and an acid in a container to obtain manganese salt particles doped with element A, where the stirring is carried out at a temperature of 20-120°C, optionally 25-80°C; and / or, the stirring is carried out at 500-700 rpm for 60-420 minutes, optionally 120-360 minutes;
[0063] Manganese salt particles doped with element A are mixed with a lithium source, a phosphorus source and a source of element R in a solvent to obtain a slurry, which is then sintered under an inert gas atmosphere to obtain lithium manganese phosphate doped with element A and element R. The sintering step is sintering at 1100-1250°C for 12-20h.
[0064] According to some embodiments of the present invention, the phosphate-based cathode material Li m A x Mn 1-y B y P 1-z C z O 4-n D n The preparation method comprises:
[0065] Dissolving a manganese source, a source of element B, and an acid in a solvent and stirring to generate a suspension of a manganese salt doped with element B, filtering the suspension and drying the filter cake to obtain a manganese salt doped with element B; wherein the stirring is performed at a temperature in the range of 60-120° C. and / or at a stirring rate of 200-800 rpm;
[0066] Adding a lithium source, a phosphorus source, a source of element A, a source of element C, a source of element D, a solvent, and the manganese salt doped with element B obtained in the previous step into a reaction container, grinding and mixing to obtain a slurry;
[0067] The slurry obtained in the above steps is transferred to a spray drying device for spray drying and granulation to obtain granules;
[0068] The particles obtained from the above steps are sintered to obtain Li m A x Mn 1-y B y P 1-z C z O 4-n D n , sintering is carried out in the temperature range of 1150-1250℃ for 10-20 hours.
[0069] If there is a coating layer, the coating layer is further formed through a sintering process. For details, please refer to the existing technology and this application will not go into details.
[0070] The manganese source, A source, lithium source, M source and X source can be selected from corresponding water-soluble salts, such as chlorides, sulfates, nitrates, organic acid salts, etc.; the phosphorus source can be selected from phosphoric acid, phosphorous acid, pyrophosphate or corresponding salts, and the ammonia source can be selected from ammonium salts.
[0071] The above-mentioned ternary positive electrode materials can be prepared by referring to the commonly used preparation methods in this field or using commercial ternary materials with existing technology, such as a series of polycrystalline ternary positive electrode materials produced by Ningbo Rongbai New Energy Technology Co., Ltd. (referred to as Rongbai Technology in the embodiment).
[0072] [Positive electrode]
[0073] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0074] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0075] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0076] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0077] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0078] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0079] [Negative electrode]
[0080] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0081] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0082] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0083] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0084] In some embodiments, the negative electrode film layer may further include a binder. For example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0085] In some embodiments, the negative electrode film layer may further include a conductive agent. For example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0086] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0087] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0088] [Electrolytes]
[0089] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0090] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.
[0091] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0092] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0093] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0094] [Isolation film]
[0095] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0096] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0097] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0098] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0099] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0100] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 with a square structure as an example.
[0101] In some embodiments, referring to Figure 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0102] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0103] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0104] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0105] In some embodiments, the battery modules described above may be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0106] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0107] In addition, the present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0108] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0109] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0110] [Example]
[0111] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0112] Sources of positive electrode materials, including phosphate positive electrode materials LiMn 0.6 Fe 0.4 PO4 was purchased from Defang Nano, ternary cathode materials were purchased from Rongbai Technology, and the remaining cathode materials were prepared using the following methods.
[0113] (1) Preparation of co-doped lithium manganese iron phosphate core
[0114] Preparation of Fe, Co and V co-doped manganese oxalate: 689.5g manganese carbonate (in MnCO3, the same below), 455.2g ferrous carbonate (in FeCO3, the same below), 4.6g cobalt sulfate (in CoSO4, the same below) and 4.9g vanadium dichloride (in VCl2, the same below) were fully mixed in a batch mixer for 6 hours. The mixture was transferred to a reactor and 5 liters of deionized water and 1260.6g oxalic acid dihydrate (in C2H2O4.2H2O, the same below) were added. The reactor was heated to 80°C and stirred at 600rpm for 6 hours until the reaction terminated (no bubbles were generated) to obtain a manganese oxalate suspension co-doped with Fe, Co, V and S. The suspension was then filtered and the filter cake was dried at 120°C and subsequently ground using an air mill. The mixture was ground, classified and sieved through a 325 mesh sieve to obtain Fe, Co and V co-doped manganese oxalate dihydrate particles.
[0115] Preparation of Fe, Co, V, and S co-doped lithium manganese iron phosphate: 1793.4 g of manganese oxalate dihydrate particles obtained in the previous step, 369.0 g of lithium carbonate (calculated as Li2CO3, the same below), 1.6 g of 60% dilute sulfuric acid (calculated as 60% H2SO4, the same below), and 1148.9 g of ammonium dihydrogen phosphate (calculated as NH4H2PO4, the same below) were added to 20 liters of deionized water. The mixture was stirred for 10 hours to mix uniformly to obtain a slurry. The slurry was transferred to a spray drying apparatus for spray drying and granulation at a setting of 250°C for 4 hours to obtain a powder. The powder was sintered at 1200°C for 16 hours in a protective atmosphere of nitrogen (90% by volume) + hydrogen (10% by volume) to obtain 1572.1 g of Fe, Co, V, and S co-doped lithium manganese iron phosphate.
[0116] Preparation Example 2: Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 Preparation
[0117] 1) Preparation of positive electrode active materials
[0118] Preparation of doped manganese oxalate: Thoroughly mix 1.3 mol of MnSO₄﹒H₂O and 0.7 mol of FeSO₄﹒H₂O in a blender for 6 hours. Transfer the mixture to a reactor, and add 10 L of deionized water and 2 mol of oxalic acid dihydrate (calculated as oxalic acid). Heat the reactor to 80°C and stir at 600 rpm for 6 hours. The reaction is terminated (no bubbles are generated), yielding an Fe-doped manganese oxalate suspension. The suspension is then filtered, and the filter cake is dried at 120°C. The mixture is then ground, graded, and passed through a 325-mesh sieve. Finally, the mixture is ground to the desired particle size to yield Fe-doped manganese oxalate particles.
[0119] Preparation of doped lithium manganese iron phosphate: Take 1 mol of the above-mentioned manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, an 85% phosphoric acid aqueous solution containing 0.999 mol of phosphoric acid, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2 and 0.005 mol of sucrose and add them to 20L of deionized water. Transfer the mixture to a sand mill and grind and stir it for 10 hours to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation, set the drying temperature to 250°C, dry it for 4 hours, and obtain particles. In a protective atmosphere of nitrogen (90 volume %) + hydrogen (10 volume %), sinter the above powder at 1150°C for 15 hours to obtain carbon-coated Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 .
[0120] The primary particle size, volume particle size distribution and specific surface area of the obtained materials were adjusted by adjusting the heating temperature of the reactor, the mesh size of the sieve and the sintering temperature of the above-mentioned Preparation Examples 1 and 2. This application will no longer describe the preparation process of each material one by one.
[0121] Among them, it was confirmed by SEM that the phosphate-based cathode material and the ternary cathode material in each embodiment were polycrystalline secondary spheres.
[0122] The particle size of the phosphate-based cathode material and the ternary cathode material in each embodiment was determined by powder laser particle size test: referring to the national standard GB / T19077-2016, wherein deionized water was used as the solvent and ultrasound was used for 5 minutes before the test.
[0123] Powder specific surface area (BET) test: The test refers to GB / T 19587-2004. Before the test, the powder is placed in a vacuum oven at 200°C and dried for ≥ 2 hours. The required amount of powder is weighed to be > 20g.
[0124] Powder primary particle size test: Confirm the primary particle size by testing the powder using SEM.
[0125] Compression test: Weigh 1.00±0.05g of material powder, record the weight data M (unit: g), and pour all the powder into the mold groove (groove area S = 1.327cm 2 ), press another steel washer flat down on the powder, with the steel column flat down, onto the washer. The height of the steel column is H0. Press to 30,000 N and hold for 30 seconds. Release the pressure and wait 10 seconds before reading the height of the steel column, H1. Compacted density = M / [(H1-H0)*S] (Phosphate-based cathode materials are compacted at 2.3 g / cm 3 about).
[0126] Gram capacity test: The button batteries prepared above were placed in a constant temperature environment of 25°C for 5 minutes, discharged to 2.5V at 0.1C, and after standing for 5 minutes, charged to 4.3V or 4.25V (Ni content > 70%, upper limit voltage is 4.25V) at 0.1C cross-flow constant voltage, and then charged at 4.3V or 4.25V at constant voltage to a current ≤0.05mA, and stood for 5 minutes. The charging capacity at this time is recorded as C0, and then discharged to 2.5V at 0.1C. The discharge capacity at this time is the initial discharge capacity, recorded as D0.
[0127] The gram capacity of the positive electrode active material is obtained by dividing the tested discharge capacity value (ie, the initial discharge capacity D0) by the mass of the positive electrode active material in the button cell.
[0128] Positive electrode ICP test
[0129] Take about 0.4g of the dry positive electrode and add 10ml of aqua regia, then place it on a hot plate and heat it to 180℃. Let it stand for 30 minutes. After the positive electrode is digested, cool it to room temperature and transfer it to a 100ml volumetric flask and make it up to volume. Take 1ml of the sample and dilute it to 100ml. Use thermometer to measure the Ni, Co, and Mn element content.
[0130] The gram capacity, D V 50. D V 90. The BET specific surface area is recorded in Table 1.
[0131] Table 1
[0132] Among them, NCM-21 is a single crystal particle, and the rest are polycrystalline particles.
[0133] The compositions of the positive electrode material compositions of the embodiments and comparative examples are shown in Table 2 (wherein the ratio of LMFP is the mass ratio of LMFP to NCM).
[0134] Table 2
[0135] The electrical performance was tested in the following manner.
[0136] (1) Preparation of mixed electrode laminate batteries:
[0137] Preparation of a hybrid positive electrode: The Class A and Class B materials described in the above examples and comparative examples were used as positive electrode active materials (the mixing ratio was based on the mass ratio of mA + mA = 100%), polyvinylidene fluoride (PVDF), and conductive carbon were added to a certain amount of N-methylpyrrolidone (NMP) in a mass ratio of 90:5:5 for active material:PVDF:conductive carbon. The mixture was stirred in a drying room to form a uniform slurry with a viscosity controlled to 3000-10000 mPa·s. The slurry was then coated on aluminum foil, dried, and cold pressed to form a positive electrode sheet.
[0138] Preparation of graphite anode: artificial graphite as the negative electrode active material, sodium carboxymethyl cellulose (CMC), conductive carbon and styrene-butadiene rubber (SBR) in a mass ratio of 94:1.5:2:2.5, add a certain amount of deionized water, and stir in a drying room to form a uniform slurry with a controlled viscosity of 2000-12000 mPa·s. The slurry is then coated on copper foil. The negative electrode coating mass is referenced to the matching relationship with the positive electrode (94% * negative electrode coating mass * graphite gram capacity = 1.15 * 90% * positive electrode coating mass * mixed positive electrode gram capacity, where the gram capacity refers to the gram capacity information of the material for the third cycle of the powder of the lithium half-cell). After drying and cold pressing, the negative electrode sheet is formed;
[0139] The electrolyte used was 1 mol / L LiPF6 / (ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC)) (volume ratio 1:1:1) + 5 wt.% fluoroethylene carbonate (FEC);
[0140] A porous polymer film made of polyethylene (PE) is used as the separator.
[0141] In the drying room, the battery cells are assembled into laminated cells for testing after processes such as electrode punching / electrode cleaning / lamination / welding / top sealing / liquid injection / pre-forming / evacuation / forming / molding.
[0142] (2) Initial gram capacity test of laminated batteries
[0143] The laminated batteries prepared above were respectively left standing for 5 min in a constant temperature environment of 25°C, discharged at 1 / 3C to 2.5V, left standing for 5 min, and then charged at a constant current of 1 / 3C with constant voltage to 4.3V or 4.25V (when the Ni content > 70%, the upper limit voltage is 4.25V), and then charged at a constant voltage of 4.3V or 4.25V until the current ≤ 0.05 mA, left standing for 5 min. The charging capacity at this time was recorded as C0, and then discharged at 1 / 3C0 to 2.5V. The discharge capacity at this time was the initial discharge capacity, recorded as D0.
[0144] Dividing the measured discharge capacity value (i.e., the initial discharge capacity D0) by the mass of the positive electrode active material in the secondary battery gives the initial full - charge specific capacity of the positive electrode active material.
[0145] (3) Cycle performance test of the secondary battery at 25°C
[0146] Each of the secondary batteries prepared above was charged at 0.5C0 to 4.3V or 4.25V in a constant temperature environment of 25°C between 2.5V and 4.3V or 4.25V, then charged at a constant voltage of 4.3V or 4.25V until the current ≤ 0.05 mA, left standing for 5 min, and then discharged at 0.5C to 2.5V. The capacity was recorded as Dn (n = 1, 2, 3...). Repeat the above operations for more than 5000 cycles, measure the capacity fade value. The capacity fade was calculated as the ratio of Dn / D3 as the cell attenuation degree (State of health SOH). Compare the number of cycles of each cell when the attenuation reaches 80% SOH as the evaluation index of the cycle ability.
[0147] (4) Charging ability experiment:
[0148] First, perform a capacity test on the soft - package laminated battery. The process is as follows: Charge at a constant current of 0.33C until the full - charge voltage V1, then switch to constant - voltage charging. When the charging current decreases to 0.05C, the constant - voltage charging ends. Subsequently, discharge at 0.33C to the full - discharge voltage V2. Repeat this process 3 times, and take the result of the 3rd time as the standard. At the same time, the positive - electrode specific capacity can be calculated using the result of the 3rd time.
[0149] Perform charging tests on the soft - package laminated battery at different rates (C1 < C2 < C3 < C4 <... < Cn). During the test, the charging rate should increase from small to large, and the full - charge voltage of the soft - package laminated battery and the negative - electrode voltage of the soft - package laminated battery should be monitored simultaneously during the charging process. The detailed process is as follows: Charge the soft - package laminated battery at C1 until the full - charge voltage V1 or the negative - electrode voltage is 0V, extract the SOC value of the battery at the end of charging, and then discharge at 0.33C to the full - discharge voltage V2. Repeat the above process to obtain the SOC values at the end of charging at different rates. The Cn at 100% SOC charging is the charging ability of the cell in this scheme.
[0150] (5) Low temperature discharge capability test
[0151] In a constant temperature environment of 25℃, let the battery stand for 30 minutes, then discharge it at a constant current of 0.33C to the lower cut-off voltage of 2.5V, let it stand for 5 minutes, charge it at a constant current of 0.33C to the upper cut-off voltage (4.4V), then charge it at a constant voltage until the current is less than 0.05C, let it stand for 5 minutes, discharge it at a constant current of 0.33C to the lower cut-off voltage of 2.5V, and record the discharge capacity at this time, which is the initial discharge capacity C0.
[0152] The battery was operated at 5°C according to the above process and the discharge capacity Cn was recorded. The discharge capacity retention rate of the battery at -5°C was calculated according to the following formula.
[0153] Low temperature discharge capability = 100% × Cn / C0
[0154] The test results are recorded in Table 3.
[0155] Table 3
[0156] From the comparison of Examples 1 to 5 in the above table, it can be seen that as the amount of phosphate-based positive electrode material decreases, the cycle life first increases and then decreases. This is because the cycle performance of the phosphate-based positive electrode material itself is improved due to the ternary positive electrode material. When the ternary positive electrode material is mixed with the ternary positive electrode material in an appropriate proportion, the lithium and iron therein play an auxiliary role in the cycle performance stability of the ternary positive electrode material. Therefore, when the content of the phosphate-based positive electrode material in the mixture of the two is greater than 80%, the cycle life of the battery is further improved; as the content of the phosphate-based positive electrode material increases, the charge and discharge capacity of the battery is gradually improved.
[0157] According to the comparison between Examples 6 to 16, Examples 21 to 24 and Example 1, it can be seen that when the D of the phosphate-based positive electrode material is controlled, V When the particle size of the primary particles of the phosphate-based cathode material is controlled to be 35 to 110 nm or when the D V When the particle size is 5-11 μm, the battery can achieve better charging and discharging capabilities.
[0158] According to the comparison of Examples 17 to 20, 34 to 26 with Example 1, it can be seen that whether the BET specific surface area of the phosphate-based positive electrode material or the BET specific surface area of the ternary positive electrode material changes, it will affect the charge and discharge capacity and cycle performance of the battery. When the BET specific surface area of the phosphate-based positive electrode material and the ternary positive electrode material is too large, the cycle performance and charging capacity will be significantly reduced.
[0159] According to the comparison of Examples 25 to 33 with Example 1, it can be seen that the Ni molar content has a significant impact on the energy density improvement of the blended material, and the Co molar content increases the electronic conductivity and ionic conductivity of the system, which can effectively improve the charge and discharge capacity of the positive electrode material.
[0160] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.
Claims
1. A positive electrode material composition, in, It includes a phosphate-based positive electrode material and a ternary positive electrode material, the weight of the phosphate-based positive electrode material is denoted as W1, the weight of the ternary positive electrode material is denoted as W2, α=W1 / (W1+W2), 50%≤α≤97%, optionally 70%≤α≤90%, the phosphate-based positive electrode material is a polycrystalline secondary spherical material and / or the ternary positive electrode material is a polycrystalline secondary spherical material.
2. The positive electrode material composition according to claim 1, in, The particle size distribution of the positive electrode material composition satisfies the following relationship: 14>Aα+B(1-α)>7, wherein A is the D of the phosphate-based positive electrode material. V 50, B is D of the ternary positive electrode material V 50.
3. The positive electrode material composition according to claim 1 or 2, in, The particle size of the primary particles of the phosphate-based positive electrode material is 10 to 600 nm, and can be 35 to 110 nm. Optionally, the laser particle size D of the phosphate-based positive electrode material is V 50 is 7~30μm, D V 50 can be selected as 8~14μm, DV 90 <30μm.
4. The positive electrode material composition according to any one of claims 1 to 3, in, The BET specific surface area of the phosphate-based positive electrode material is 8-20 m 2 / g.
5. The positive electrode material composition according to any one of claims 1 to 4, in, The chemical formula of the phosphate-based positive electrode material is Li 1+x Mn 1-y A y P 1-z R z O 4 , wherein x is any value in the range of -0.100-0.100, y is any value in the range of 0.001-0.500, and z is any value in the range of 0.001-0.100, and the values of x, y and z satisfy the following conditions: the chemical formula is electrically neutral; A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can be one or more elements selected from Fe, Ti, V, Ni, Co and Mg, and R is one or more elements selected from B, Si, N, S, F, Cl and Br, and optionally, R is an element selected from B, Si, N and S; Alternatively, the chemical formula of the phosphate-based cathode material is Li a A x Mn 1-y B y P 1-z C z O 4-n D n , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W, B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, C includes one or more elements selected from the group consisting of B (boron), S, Si and N, D includes one or more elements selected from the group consisting of S, F, Cl and Br, a is selected from the range of 0.9 to 1.1, x is selected from the range of 0.001 to 0.1, y is selected from the range of 0.001 to 0.5, z is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, and the phosphate-based positive electrode material is electrically neutral.
6. The positive electrode material composition according to claim 5, in, The phosphate-based positive electrode material comprises a polycrystalline core and a coating layer covering the polycrystalline core, wherein the polycrystalline core comprises a 1+x Mn 1-y A y P 1-z R z O 4 The material or the chemical formula Li a A x Mn 1-y B y P 1-z C z O 4-n D n The coating layer may optionally be one or more layers of pyrophosphate, phosphate, or carbon.
7. The positive electrode material composition according to any one of claims 1 to 6, in, The D of the ternary cathode material V 50 is 5~11μm, D V 99≤30μm; Optionally, the average particle size of the primary particles of the ternary positive electrode material is 50-800nm.
8. The positive electrode material composition according to any one of claims 1 to 7, in, The BET specific surface area of the ternary positive electrode material is 0.2 to 1.2 m 2 / g.
9. The positive electrode material composition according to any one of claims 1 to 8, in, The ternary positive electrode material is an NCM ternary positive electrode material or an NCA ternary positive electrode material. Optionally, the Ni molar content of the ternary positive electrode material is 50% to 75%, and the Co molar content is 0.5% to 49.5%; further optionally, the Ni molar content is 50% to 70%, and the Co molar content is 5% to 35%.
10. The positive electrode material composition according to claim 9, in, The ternary cathode material has the chemical formula Li a’ Ni b’ Co c’ M1 d’ M2 e’ O f’ R′ g’ , where 0.75 ≤ a’ ≤ 1.2, 0 < b’ < 1, 0 < c’ < 1, 0 < d’ < 1, 0 ≤ e’ ≤ 0.2, 1 ≤ f’ ≤ 2.5, 0 ≤ g’ ≤ 1, f’ + g’ ≤ 3, M1 is Mn element and / or Al element, M2 is one or more elements selected from Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R′ is one or more elements selected from N, F, S, Cl.
11. A secondary battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material, in, The positive electrode active material is the positive electrode material composition according to any one of claims 1 to 10.
12. An electrical device comprising a secondary battery, in, The secondary battery is selected from the secondary battery described in claim 11.
Citation Information
Patent Citations
Mixed positive electrode material, positive plate using the same, and lithium ion battery
CN104300123A
Positive electrode active material, electrochemical device, and electronic apparatus
CN115020696A
Ternary co-doped lithium manganese iron phosphate material as well as preparation method and application thereof
CN115799481A
Positive electrode for lithium-ion secondary battery, production process for the same, and lithium-ion secondary battery
US20180053936A1
